Untapped Potential of Manufacturing MSEs in Bali Amidst the Covid-19 Pandemic - Candrawati, Ida Ayu; Purwanti, Putu Ayu Pramitha (Signifikan: Jurnal Ilmu Ekonomi, 2023)
The macro health impact of the COVID-19 pandemic that resulted in an economic slump in Bali exposed the need for economic development outside the tourism sector. Manufacturing Micro and Small Enterprises (MSEs) is one sector that contributes significantly to the economy, export value, and employment, particularly during moments when the tourism sector is down. This study aims to determine the performance of manufacturing MSEs during 2018-2021 using Cobb-Douglas stochastic frontier production function analysis. The Technical Inefficiency (TE) value of manufacturing MSEs in Bali was 22.24% over 2018-2021. The impact of COVID-19 on each ISIC and business location has a varied impact on the production value of MSEs Manufacturing. The gender of the business owner, financial service, age of workers, and source of raw materials are inefficiency variables that significantly affect production value. However, the training received by manufacturing MSEs had no significant effect. The findings from this study can be used as a basis for government policy in further developing the untapped potential of manufacturing MSEs in Bali regarding impacts upon Bali's tourism sector during the pandemic.JEL Classification: D24, E23, J16, L86, O14 How to Cite:Candrawati, I.A., & Purwanti, P.A.P. (2023). Untapped Potential of Manufacturing MSEs in Bali Amidst the Covid-19 Pandemic. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 383-398. https://doi.org/10.15408/sjie. v12i2.32389.